Pressurised intraperitoneal aerosol chemotherapy: rationale, evidence, and potential indications. Issue 7 (July 2019) - Alyami, Mohammad; Hübner, Martin; Grass, Fabian; Bakrin, Naoual; Villeneuve, Laurent; Laplace, Nathalie; Passot, Guillaume; Glehen, Olivier; Kepenekian, Vahan
Summary: Pressurised intraperitoneal aerosol chemotherapy (PIPAC) was introduced as a new treatment for patients with peritoneal metastases in November, 2011. Reports of its feasibility, tolerance, and efficacy have encouraged centres worldwide to adopt PIPAC as a novel drug delivery technique. In this Review, we detail the technique and rationale of PIPAC and critically assess its evidence and potential indications. A systematic search was done to identify all relevant literature on PIPAC published between Jan 1, 2011, and Jan 31, 2019. A total of 106 articles or reports on PIPAC were identified, and 45 clinical studies on 1810 PIPAC procedures in 838 patients were included for analysis. Repeated PIPAC delivery was feasible in 64% of patients with few intraoperative and postoperative surgical complications (3% for each in prospective studies). Adverse events (Common Terminology Criteria for Adverse Events greater than grade 2) occurred after 12–15% of procedures, and commonly included bowel obstruction, bleeding, and abdominal pain. Repeated PIPAC did not have a negative effect on quality of life. Using PIPAC, an objective clinical response of 62–88% was reported for patients with ovarian cancer (median survival of 11–14 months), 50–91% for gastric cancer (median survival of 8–15 months), 71–86% for colorectal cancer (median survival of 16 months), and 67–75% (median survival of 27 months) for peritoneal mesothelioma. From our findings, PIPAC has been shown to be feasible and safe. Data on objective response and quality of life were encouraging. Therefore, PIPAC can be considered as a treatment option for refractory, isolated peritoneal metastasis of various origins. However, its use in further indications needs to be validated by prospective studies.